2006
DOI: 10.1038/sj.hdy.6800839
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of wild Hops, Humulus lupulus L.

Abstract: We have analysed wild hops collected widely from the Northern Hemisphere, assessing the genetic diversity and the geographical distribution of haplotypes, to investigate the evolution and phylogeny of hops, Humulus lupulus. The haplotypes were characterized by the nuclear ribosomal DNA spacer region (length and DNA sequence) and chloroplast DNA noncoding regions (DNA sequences). The results indicated that primary divergence into European (including Caucasus and Altai hops), and Asian-North American types, was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
60
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 27 publications
6
60
0
Order By: Relevance
“…Germplasm group F, depicted on the Fitch-Margoliash tree, is similar to groups of native NA hops, for which high differentiation from wild European hops and from cultivated hops containing either EU or NA germplasm, has been shown (Stevens et al 2000;Henning et al 2004;Jakše et al 2004;Murakami et al 2006aMurakami et al , 2006b. Cultivated NA germplasm has also been defined in other studies as a group containing a high number of accessions with predominant NA germplasm in their pedigree (Sustar-Vozlic and Javornik 1999;Seefelder et al 2000;Jakse et al 2001).…”
Section: Microsatellite Diversitymentioning
confidence: 92%
See 2 more Smart Citations
“…Germplasm group F, depicted on the Fitch-Margoliash tree, is similar to groups of native NA hops, for which high differentiation from wild European hops and from cultivated hops containing either EU or NA germplasm, has been shown (Stevens et al 2000;Henning et al 2004;Jakše et al 2004;Murakami et al 2006aMurakami et al , 2006b. Cultivated NA germplasm has also been defined in other studies as a group containing a high number of accessions with predominant NA germplasm in their pedigree (Sustar-Vozlic and Javornik 1999;Seefelder et al 2000;Jakse et al 2001).…”
Section: Microsatellite Diversitymentioning
confidence: 92%
“…The pedigree of the other two cultivars with more than 90% E ancestry was unknown, or too complex for interpretation, but the assumption of a high proportion of native NA germplasm is supported by previous molecular and quality data. Only the proportion of native NA germplasm in the wild Japanese accession in germplasm group E could not be well explained, because of its wild origin and the unresolved overall relationship of Japanese wild hops to NA and EU wild hops (Murakami et al 2006a(Murakami et al , 2006b. However, we assumed that E ancestry or germplasm group E represents a specific hop germplasm which has been created by introgression of native NA germplasm into EU hops through hybridization and artificial selection.…”
Section: Hop Genetic Structurementioning
confidence: 97%
See 1 more Smart Citation
“…These SSRs were used for cultivar identification (Brady et al 1996;Cerenak et al 2004), genetic diversity evaluation among wild and cultivated hop Murakami et al 2006b), and for genetic mapping (Č erenak et al 2006). Sixty primer pairs were recently developed from six hop genomic-enriched libraries (Stajner et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Studying of hop wild gene pool is of essential need for sustainability of hop production (Nesvadba 2007). Cytogenetic and molecular studies of wild hops have brighten up the phylogeny of hops (Ono 1961, Henning et al 1997, Hampton et al 2001, Hampton et al 2002, Jakše et al 2004, Murakami et al 2006, Lutz et al 2007, Nesvadba 2007, Probasco et al 2007, but a few authors reported on phenotypic variability of wild hop populations (Wormald 1915, Schmidt 1917, Salmon and Wormald 1921, Blattny 1950, Davis 1957, Ono 1961, Wagner 1974and 1975, Nesvadba 2007. However, phenotypic characterization of hop plants is the very first step that precedes the mentioned molecular analyses.…”
mentioning
confidence: 99%